Vitamin-D Deficiency As a Potential Environmental Risk Factor in Multiple Sclerosis, Schizophrenia, and Autism - Kočovská, Eva; Gaughran, Fiona; Krivoy, Amir; Meier, Ute-Christiane (Frontiers in Psychiatry, 2017)
In this short review we want to summarize the current findings on the role of vitamin-D in multiple sclerosis, schizophrenia and autism. Many studies have highlighted hypovitaminosis-D as a potential environmental risk factor for a variety of conditions such as multiple sclerosis, asthma, cardiovascular disease and more recently psychiatric diseases. However, whether hypovitaminosis-D is a potential causative factor for the development or activity in these conditions is currently unknown. Here we will discuss current evidence exploring the role of vitamin-D in multiple sclerosis, schizophrenia and autism and its impact on adaptive and innate immunity, antimicrobial defence, the microbiome, neuroinflammation, behaviour and neurogenesis. More work is needed to gain insight into its role in the underlying pathophysiology of these conditions as it may offer attractive means of intervention and prevention.